The study of language - Yule, George, 1947- (Cambridge, UK : Cambridge University Press, 2016)
"This bestselling textbook provides an engaging and user-friendly introduction to the study of language. Assuming no prior knowledge of the subject, Yule presents information in bite-sized sections, clearly explaining the major concepts in linguistics through all the key elements of language. This sixth edition has been revised and updated throughout, with substantial changes made to the chapters on phonetics, grammar and syntax, and the addition of 30 new figures and tables and 80 new study questions. To increase student engagement and to foster problem-solving and critical thinking skills, the book also includes 20 new tasks. An expanded and revised online study guide provides students with further resources, including answers and tutorials for all tasks, while encouraging lively and proactive learning. This is the most fundamental and easy-to-use introduction to the study of language"--
"In Charles Darwin's vision of the origins of language, early humans had already developed musical ability prior to language and were using it "to charm each other." This may not match the typical image that most of us have of our early ancestors as rather rough characters wearing animal skins and not very charming, but it is an interesting speculation about how language may have originated. It remains, however, a speculation. We simply don't know how language originated. We do know that the ability to produce sound and simple vocal patterning (a hum versus a grunt, for example) appears to be in an ancient part of the brain that we share with all vertebrates, including fish, frogs, birds and other mammals. But that isn't human language. We suspect that some type of spoken language must have developed between 100,000 and 50,000 years ago, well before written language (about 5,000 years ago). Yet, among the traces of earlier periods of life on earth, we never find any direct evidence or artifacts relating to the speech of our distant ancestors that might tell us how language was back in the early stages. Perhaps because of this absence of direct physical evidence, there has been no shortage of speculation about the origins of human speech"--
Machine generated contents note: Preface; 1. The origins of language; 2. Animals and human language; 3. The sounds of language; 4. The sound patterns of language; 5. Word-formation; 6. Morphology; 7. Grammar; 8. Syntax; 9. Semantics; 10. Pragmatics; 11. Discourse analysis; 12. Language and the brain; 13. First language acquisition; 14. Second language acquisition/learning; 15. Gestures and sign languages; 16. Written language; 17. Language history and change; 18. Regional variation in language; 19. Social variation in language; 20. Language and culture; Glossary; References; Index.
Previous ed.: 2014.
Keywords: Language and languages; Linguistics